INOVASI PELAYANAN PUBLIK: ANALISIS BIBLIOMETRIK TERHADAP PERKEMBANGAN DAN TREN PENELITIAN - Monica, Reza; Permatasari, Indah; Lionardo, Andries; Budiyanto, M. Nur (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2024)
This research presents a bibliometric analysis of the development and collaboration in public service innovation research from 2014 to 2023. Data were obtained from the Scopus database using the keyword "Public Services Innovation." The results indicate a significant increase in the number of articles discussing public service innovation each year, with articles being the dominant document type. The study also identifies leading authors in the field, with Gallouj and Djellal leading in both the number of studies and citations received. Co-authorship network analysis reveals two clusters of authors showing close collaboration in public service innovation research. Furthermore, visualization of inter-country networks highlights patterns of cross-border collaboration, with some countries tending to collaborate more closely in this research. Keyword clustering provides insights into themes and trends in research, focusing on information technology, innovation management, service design, and public sector collaboration. Overlay and density visualization analyses deepen the understanding of the relationships between themes and the evolution of research over time. Recommendations include promoting cross-border collaboration, focusing on innovation management and leadership, and researching technology to enhance public services. Further research is expected to identify current research trends and areas for expansion.